A39 A META-ANALYSIS OF COLON CLEANSING PREPARATIONS IN PATIENTS WITH INFLAMMATORY BOWEL DISEASE. (1st March 2018) - Restellini, S; Kherad, O; Bessissow, T; Ménard, C; Martel, M; Barkun, A N
Abstract: Background: Patients with inflammatory bowel disease (IBD) are subject to several colonoscopies during their lifespan and subsequently several bowel preparations. Recent guidelines endorse the use of split-dose regimens, but only few data are available in IBD patients who are often excluded from trials for safety concerns. Aims: We performed a systematic review and meta-analysis to determine any existing difference in terms of effectiveness, safety and tolerability between existing colon-cleansing products in the IBD population. Methods: Systematic searches were performed (January 1980 - September 2016) using MEDLINE, EMBASE, Scopus, CENTRAL and ISI Web of knowledge for randomized trials assessing preparations with or without adjuvants, given in split and non-split dosing, in high (>3L) or low-volume (2L or less) regimens. Bowel cleansing quality was the primary outcome. Secondary outcomes included patient willingness-to-repeat the preparation and side effects and complications. Results: Out of 439 citations, 4 trials fulfilled our inclusion criteria (n = 449 patients). One trial (Lazzaroni et coll. 1993) assessed the impact of adding Simethicone to Polyethylene Glycol (PEG) 4L witch resulted in similar bowel cleansing effect but a better willingness to repeat. One other trial (Gould et coll 1982) compared senna to castor oil, again without any difference in term of bowel cleansing. Two trials compared the efficacy of PEG high-volume versus PEG low-volume associated to an adjuvant in split-dose regimens (Kim et al 2016, Manes et al 2016): PEG low-dose efficacy was not different to PEG high-dose; OR=0.84 (0.37; 1.92) A higher proportion of patients were willing to repeat low-volume preparations vs high-volume; OR 5.11 (1.31–20.0). Conclusions: In IBD population, PEG low-volume regimen seems not inferior to PEG high-volume to clean the colon, and yields improved tolerance. Further additional research is urgently required to compare contemporary products in this specific population. Funding Agencies: None